An Exploration of the Impact of the "Open Gym" Scheduling Model of Cardiovascular Rehabilitation on Completion, Attendance, and Health Outcomes. Issue 1 (January 2019) - Whited, Matthew C.; Ellis, Jordan M.; Freeman, John Taylor; Corson, Ansley T.; Greenway, Stacey B.; Busch, Andrew M.; Whited, Amanda L.; Sears, Samuel F.
Abstract : Purpose: To explore the effects of implementation of the "Open Gym" (OG) scheduling model of cardiovascular rehabilitation administration on the rate of patient engagement and change in commonly measured clinical outcomes. Little data exist on the potential benefits of the OG model on patient completion, attendance, and clinical outcomes. Methods: A retrospective chart review was conducted that included the 1-y period both before and after OG model implementation. Bootstrapped regression and analysis of variance were utilized to determine (1) whether the scheduling model is associated with number of sessions attended and program completion, and (2) among those who meet their goals and thus complete the program, if the scheduling model predicts change in cardiovascular rehabilitation clinical outcomes (ie, percent weight change, 6-min walk distance, and peak metabolic equivalents during exercise) when controlling for baseline values. Follow-up analyses controlled for and explored interactions related to age, race, and sex. Results: In this racially diverse sample (34% nonwhite), patients under either the OG model (n = 125) or the Traditional model (n = 82) attended an equivalent number of sessions and were just as likely to complete their treatment. However, clinical outcomes favored the Traditional model, even as more patients participated in the OG model, especially racial minority patients. Conclusions: Although the OG model is more consistent with patient-centered care, gains in functional capacity may be diminished. Furthermore, better controlled experiments are needed to examine the effects of implementing the OG model and should include measures of possible mechanisms influencing racial differences. Abstract : Comparing the Open Gym scheduling model of cardiovascular rehabilitation with the Traditional model demonstrated equivalent attendance and completion rates. However, clinical outcomes favored the Traditional model. As more facilities implement this model, outcomes should be closely monitored to confirm and determine mechanisms of any detrimental effects.